Students' Perception towards the Use of ChatGPT as a Tool for Learning English - Meluwu, Donny Febrian Erens; Neman, Meily Ivane Esther (Global Education Journal, 2025)
This study aimed to explore students' perception towards the use of ChatGPT as a tool for learning English, particularly the Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). The study was conducted at a 10th-grade senior high school, SMA Negeri 1 Airmadidi, that involved 112 respondents. The research design was descriptive with a quantitative methodology. The instrument was a questionnaire with 16 items. The findings indicated that: (a) On average percentage, 75.65% of students have a positive perception of ChatGPT’s usefulness. (b) Likewise, on average percentage 72.58% of students also show a positive perception about its ease of use. Thus, most of the students show a positive perception about ChatGPT’s usefulness and ease of use as an English learning tool. Therefore, for recommendation: (a) Firstly, it tells teachers about students’ positive perceptions of its usefulness and Ease of use. Therefore, it can be incorporated into education. (b) Secondly, ChatGPT is recommended for students to improve their learning process, particularly in English. (c), Lastly, the researcher or others can do additional research to see whether using ChatGPT improves students' English achievement and mastery.